Analysis of Joint Property Division in Mixed Marriages: A Case Study of The Supreme Court Decision Number 1400 K/Pdt/2017 Perspective of International Private Law - Sofiyana, Nurani; Prastyanti, Rina Arum (The Easta Journal Law and Human Rights, 2024)
This study seeks to evaluate the effectiveness of Indonesia's Law Number 1 of 1974 on Marriage, specifically concerning the division of joint property in mixed marriages that involve aspects of international civil law. Supreme Court Decree Number 1400 K/Pdt/2017 offers a key reference point, showcasing how Indonesian law has been applied to govern property division in these cases. The study applies a normative juridical approach to examine legal norms and standards, including legislative analysis of the Marriage Act and the Basic Agrarian Law. It also uses case-based methods to assess international civil law's impact, such as the principle of lex situs, which mandates that immovable property like land be governed by the laws of its location. This Supreme Court ruling reveals an attempt to balance Indonesian law with foreign property rights, ensuring that foreign nationals’ rights are acknowledged in property division. Such cases underscore the importance of reforming Indonesia’s mixed marriage laws to enhance legal clarity and fairness for all parties.